Questions of reality: a review of the play Through the Reading Glasses - Woolsey, Leny (Organizational Aesthetics, 2015)
When I started reading this play I was glad that, only a few days before, I had read an abridged version of Alice in Wonderland to my daughter as a bedtime story. I was instantly comfortable recognising characters, such as Con and Div, who are loosely based on Tweedle Dum and Tweedle Dee from Lewis Carroll’s classic. I couldn’t work out whether the Help Avatar was supposed to resemble the Caterpillar or the Cheshire Cat, but it didn’t matter, as the parallels with Wonderland faded away and I became more deeply engaged with the "real" story of the Professor and his journey Through the Reading Glasses (TTRG).